Kinetic Study of Hydrogenation of Fatty Acid Methyl Ester into Fatty Alcohol over Rhenium–Niobia and Rhenium–Alumina Catalysts - Gunawan, Melia L.; Rasrendra, Carolus B.; Addarojah, Zaqiyah; Suherman, Muhammad F.; Perkasa, Sayoga; Kadja, Grandprix T. M. (Arabian journal for science and engineering (2011), 2024)
Fatty alcohols can be generated by hydrogenating fatty acid methyl ester (FAME) using a heterogeneous catalyst. Among diverse alternatives, precious metal-based catalysts such as Re/Nb 2 O 5 and Re/Al 2 O 3 have exhibited superior performance. However, the kinetic study of hydrogenation FAME employing a Rhenium-based catalyst (Re) has not been investigated. Notably, kinetic studies are crucial for performance improvement and reactor design. As a result, the kinetics of the FAME hydrogenation process over these catalysts were studied and modeled comprehensively. The results demonstrate that the reaction with the Re/Nb 2 O 5 catalyst has an order of 0.77 to FAME and 1.48 to hydrogen gas, with an Arrhenius constant of 18.55 bar −1.48 M 0.23 min −1 and an activation energy of 64.44 kJ mol −1 . The Re/Al 2 O 3 catalyst has an order of 0.67 to FAME and 1.15 to hydrogen, with an Arrhenius constant of 1057.89 bar −1.15 M 0.33 min −1 and an activation energy of 78.32 kJ mol −1 . The Re/Al 2 O 3 catalyst is more sensitive to temperature changes than the Re/Nb 2 O 5 catalyst. Meanwhile, the Re/Nb 2 O 5 catalyst is more sensitive to pressure changes than the Re/Al 2 O 3 catalyst.